Implementation of Child-Friendly Inclusive Education Policy in Pekanbaru Public Elementary Schools - Muthiah Muthiah; Rita Kurnia; Azra Aibonotika (FKIP - Universitas Riau, 2026)
This study aims to analyze the implementation of the Child-Friendly Inclusive Education Policy in Pekanbaru Public Elementary Schools, identifying how the policy is implemented in the process of admitting students with special needs, curriculum implementation, provision of child-friendly facilities and infrastructure, and the roles of the government, school committees, community organizations, and professionals. This study also aims to explore the supporting factors and obstacles that arise in the implementation of the policy, and assess the extent to which the policy has an impact on educational services for students with special needs (PDBK). This research uses a qualitative approach with a policy research method (policy research). Data were collected through in-depth interviews with school principals, class teachers, special assistant teachers (GPK), the Head of the Curriculum Section of the Education Office, and PDBK parents. In addition, this study also utilized field observations and documentation studies of regulations, implementation guidelines, curricula, and school administrative documents regarding the implementation of inclusion. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to determine the alignment between policies, implementation in the field, and the results achieved. The findings of this study are expected to provide a comprehensive picture of the effectiveness of implementing child-friendly inclusive education policies in Pekanbaru Public Elementary Schools and produce recommendations for strengthening the program, both for schools and local governments.